Fish oil and probiotic food supplements: consumptions and attitudes of pregnant women in four European countries - Jaakkola, Kristiina; Koivuniemi, Ella; Hart, Kathryn; Mazanowska, Natalia; Roccaldo, Romana; Censi, Laura; Egan, Bernadette; Mattila, Lilja; Buonocore, Pasquale; Loyttyniemi, Eliisa; Raats, Monique; Ruggeri, Stefania; et al. (SPRINGER HEIDELBERG, 2025)
Purpose: Fish oil and probiotic supplements may be of benefit during pregnancy, but no information on their use across geographically and socioeconomically diverse countries exists. Our aim was to investigate (1) usage of fish oil and probiotic food supplements by pregnant women, (2) awareness amongst pregnant women of the prevailing recommendations and (3) the characteristics of the users and their beliefs regarding potential health effects of food supplement use, and to compare these variables between women from four European countries.
Methods: The survey was carried out by online questionnaires (n = 1780) in Finland (n = 536), Italy (n = 539), Poland (n = 584), and the United Kingdom (UK) (n = 121). Product information of the supplements used was collected from participants (n = 1356).
Results: Of the participants 49% (n = 670) used fish oil, and 10% (n = 132) used probiotic supplements. The median intake of DHA in the studied countries was 220 (IQR 200-600) mg/d. Users of these supplements were most likely from Finland and primiparous. Recommendations related to fish oil supplement use were most well-known in Poland, where over half knew that fish oil supplements are recommended to be consumed during pregnancy in Poland. Finnish women were most likely to know that there is no recommendation for pregnant women for use of probiotic supplements.
Conclusion: Half of the pregnant women used fish oil supplements, while probiotic use was less frequent. Not all pregnant women were familiar with the prevailing recommendations or potential health effects, which should be considered in the diet counselling provided during future health care visits.